Volume 3: Ceramics; Coal, Biomass, Hydrogen, and Alternative Fuels 2020
DOI: 10.1115/gt2020-16084
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation Into the Impact of Injector Geometrical Design Parameters on Hydrogen Micromix Combustion Characteristics

Abstract: Hydrogen micromix combustion is a promising concept to reduce the environmental impact of both aero and land-based gas turbines by delivering carbon-free and ultra-low-NOx combustion without the risk of autoignition or flashback. As a part of the ENABLEH2 project, the current study focuses on the influence of design parameters on the micromix hydrogen combustion injectors. This study provides deeper insights into the design space of a hydrogen micromix injection system via numerical simulations. The key geomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This project explores feasibility of liquid hydrogen as an aircraft fuel and includes the fuel system as well. The micromix development focuses on Reynolds-averaged Navier-Stokes (RANS) and large eddie simulations (LES) adapted for micromix hydrogen combustion and their limitations [15][16][17][18][19], the design of the micromix geometry [20,21], and thermoacoustic modeling [22][23][24].…”
Section: Stationary Gas Turbine Combustionmentioning
confidence: 99%
See 2 more Smart Citations
“…This project explores feasibility of liquid hydrogen as an aircraft fuel and includes the fuel system as well. The micromix development focuses on Reynolds-averaged Navier-Stokes (RANS) and large eddie simulations (LES) adapted for micromix hydrogen combustion and their limitations [15][16][17][18][19], the design of the micromix geometry [20,21], and thermoacoustic modeling [22][23][24].…”
Section: Stationary Gas Turbine Combustionmentioning
confidence: 99%
“…This airgate shape was chosen for this paper, too. Sun et al [17] varied the airgate shape and showed the beneficial effect of a pair arrangement for the flame structure. Placing the blunt side of the airgates towards each other as shown in Fig.…”
Section: Micromix Geometry Definitionmentioning
confidence: 99%
See 1 more Smart Citation